Building Students’ Creative Thinking Skills in Science Learning : A Systematic Review of STEM-Based Approaches - Ramadhani, Nisfil Amelia; Hardianti, Risa Dwita (Jurnal Paedagogy, 2025)
This study aims to examines the effectiveness of the STEM approach in building students' creative thinking skills in science education, focusing on its implementation to meet students' needs in facing 21st-century challenges. This study employed a systematic literature review method adapted from PRISMA framework guidelines. Qualitative data collection techniques were employed, followed by thematic analysis for data interpretation. The literature analyzed was indexed in the Scopus and Google Scholar databases, with a publication range from 2022 to 2024. The study results found that using STEM effectively builds students' creative thinking skills in science learning.. The STEM approach enhances students’ comprehension of scientific ideas and motivates them to solve problems using critical and creative thinking. According to the results study, incorporating science, technology, engineering, and mathematics components into science instruction enables students to collaborate, innovate, and apply their knowledge in real-world contexts. Additionally, factors such as teacher support, resource availability, and a conducive learning environment are crucial in successfully implementing this approach. This study has implications for developing more effective curriculum and teaching strategies to enhance students’ creative thinking skills. The long-term effects of the STEM method on students’ academic performance and capacity for creative thought in many educational situations require more investigation.